The workforce of the future: an assessment of technology proficiency (London, 2015)
"There is growing pressure on companies, governments and other employers to identify, attract and retain human talent capable of leveraging technology effectively and efficiently. The difficulties in engaging such workers stem from numerous factors, including globalisation, changing demographics and emerging technologies such as artificial intelligence and the Internet of Things. The challenges facing organisations from the technology and human resources perspective vary across countries and regions; however, most countries, regardless of their stages of development, are becoming more digitised. As countries increase their connectivity infrastructures, and as technology pervades society and production continues to be automatised, the workplace also becomes more technological. This change requires a new type of employee, a technologically savvy employee, one of the “Workforce of the Future”."